(3fhGOQ Ydj Hf CSHGWs - (3Gdchaj, CHh GdMSf, , Ydj Hf CSHGW Hf SGde, J b (B9 (3g`s ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3HSe Gddg (B... (3bGd MOKfG CHh GdYHGS CMeO Hf eMeO Hf SYjO GdgeOGfj bGd GNHQfG Ydj Hf GdMSf jf aVGd Yf Ydj Hf CSHGW bGd GNHQfG Ydj Hf GdMSf Hf aVGd Yf Ydj Hf CSHGW (B...s
(3BNQgG (B:s
... (3Ke jNQL QLd CTbQ Ph SHGd jfUH dg cQSj Ydi HGH OGQ YeQ Hf MQjK jOYhG Edi GdHQGAI ef Ydj Hf CHj WGdH Ydjg GdSdGe hjbJd NdbG ef GdNdb hjbJd aj jheg aQCjfG Pdc (B. (3Jes
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\404s
(3gOjI GdYGQajf (B1 \673s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs